Possible Application of Raman Microspectroscopy to Verify the Interstitial Cystitis Diagnosis after Potassium Sensitivity Test: Phenylalanine or Tryptophan as a Biomarker. Issue 3 (6th June 2013) - Hsieh, Tzu-Feng; Yu, Ken-Jen; Lin, Shan-Yang
Abstract : There is lack of a worldwide standard technique for clinical diagnosis of interstitial cystitis (IC). Raman spectroscopy with higher specificity and sensitivity has been extensively used to act as a non-destructive analytical technique without special sample preparation. In this preliminary study, possible use of Raman microspectroscopy as an IC diagnostic tool was attempted. Twenty-two participants were screened by clinical features, history, urodynamic evaluations and potassium sensitivity test (PST). The freeze-dried water samples voided from all the participants after PST were directly determined by using a confocal Raman microspectroscopy to search the biomarker. Participants with or without IC symptom were separated into control and clinical groups, according to the above screening. The participants in the clinical group were further divided into mild and severe subgroups by PST. The symptom of urinary pain and urgency was significant difference between the mild and severe subgroups ( p < 0.05). A significant increase in urinary frequency but a marked reduction in bladder capacity, maximum cystometric capacity and maximum voiding flow rate were obtained for clinical group of IC participants, as compared with the result of control group ( p < 0.05). By using Raman microspectroscopic determination, the band near 1003 or 1005 cm −1 assigned to phenylalanine was respectively detected from the freeze-dried water sample of control group or mild subgroup, but the band at 1010 cm −1 due to tryptophan was found in the freeze-dried water sample of severe subgroup. The result of this preliminary study first suggests a possible application of Raman microspectroscopy to strongly certify the results of PST for IC diagnosis. Phenylalanine or tryptophan might be acted as a biomarker to assist the diagnosis of IC after PST. Particularly, the appearance of tryptophan might be used to discriminate the severity of IC symptom.